The NIa-Protease Protein Encoded by the Pepper Mottle Virus Is a Pathogenicity Determinant and Releases DNA Methylation of Nicotiana benthamiana - Gong, Yi-Nuo; Tang, Ru-Qing; Zhang, Yu; Peng, Jing; Xian, OuYang; Zhang, Zhan-Hong; Zhang, Song-Bai; Zhang, De-Yong; Liu, Hui; Luo, Xiang-Wen; Liu, Yong (Frontiers in Microbiology, 2020)
It is well documented that the canonical function of NIa-protease (NIa-Pro) of the potyviruses is responsible for cleaving the viral polyprotein into functional proteins. Although NIa-Pro is vital for the infection cycle of potyviruses, the function of NIa-Pro in the interaction of the potyvirus host is not clear. In this study, NIa-Pro is ectopically expressed from a potato virus X (PVX) vector and infiltrates Nicotiana benthamiana wild type and 16-TGS. The pathogenicity and inhibition of host transcriptional gene silencing (TGS) are characterized. Ectopic expression of NIa-Pro from a PVX vector resulted in severe mosaic symptoms followed by a hypersensitive-like response in N. benthamiana. Furthermore, PepMoV NIa-Pro was able to reverse established TGS of a green fluorescent protein transgene by reducing methylation of promoter sequences in N. benthamiana and possessed the capacity to interfere with the global methylation of N. benthamiana. Taken together, the results of this study likely suggest that PepMoV NIa-Pro is a pathogenicity determinant and a potent suppressor of host TGS and suggest that NIa-Pro may employ novel mechanisms to suppress host antiviral defenses. To the best of our knowledge, this is the first report of a plant RNA virus modulating host TGS in a novel manner by interfering with the establishment of the methylation step of the plant DNA methylation pathway.